Les images des passions adolescentes - Christel Gumy (Revue d'anthropologie des connaissances)
Neuroscience research using sets of pictures of facial affect to test the emotional reactions of teenagers with fMRI has participated to construct a neurobiological model of adolescence. This model postulates that the particular brain configuration of young people indicates a lack of emotional control. This model tends to prevail in the sciences of adolescence, particularly in connection with the issue of risk taking. This paper investigates the process by which cognitive neuroscience, by using photographic portraits of actors mimicking emotions in fMRI studies, has produced valid stimuli that help to make visible a cerebral difference between adolescents and adults, as well as between girls and boys, in the management of emotional information. In effect, the adolescent emotional brain is constructed along two embedded hierarchies: if the age difference is the founding hierarchy, within that, sex at times act as a driving factor and at times as a moderating one.